Follicle-like niches outside the cortex? 3D phase-contrast µCT revealed medullary B cell nodules in mucosa-draining lymph nodes - Schütz, Paul; Schwarzenberg, Florian L.; Weber, Lennert J.; Hammel, Jörg U.; Siebels, Bente; Nissen, Paula; Leising, Nenya; Jarick, Katja J.; Walkenfort, Bernd; Irvine, Sarah C.; Bartl, Jasmin; Herzen, Julia; et al. (Frontiers in Immunology, 2025)
This study identifies and characterizes previously unrecognized medullary B cell niches within murine mucosa-draining lymph nodes (LNs), challenging the conventional understanding of LN architecture. Utilizing advanced imaging techniques, including synchrotron radiation-based phase-contrast micro-computed tomography (SRµCT), correlated high-resolution electron microscopy and immunohistochemistry (IHC), we revealed spherical to ovoid structures termed nodules, being distinct lymphoid compartments consistently localized in the medullary region of mandibular and other mucosa-draining LNs. These nodules were primarily composed of unswitched, non-proliferative CD45R+ B cells expressing IgD and IgM, lacking germinal center features or typical activation markers. They were seamlessly integrated into the medullary architecture, surrounded by LYVE-1+ lymphatic endothelial cells, and situated in close proximity to medullary high endothelial venules (HEVs), revealed by PNAd staining. Under steady-state conditions, this has not been previously observed in the medullary compartment of LNs but is likely facilitating nodule-like B cell aggregation in mucosa-draining LNs due to sustained low level antigenic stimulation common in mucosal environments and is underpinned by proteomics. Additionally, the nodules displayed a capillary network that closely resembles the vascularization seen in conventional B cell follicles revealed by SRµCT. Nodule formation occured between two and four weeks postnatally, thus emerging later than B cell follicles, and their abundance showed a tendency to increase with age. Functionally, these nodules appear to represent a quiescent B cell niche, potentially supporting B cell homeostasis, tolerance, or memory-like readiness, and are distinct from pathological hyperplasias. Their preservation in aged LNs, coupled with the absence of lipomatosis, suggests a role in maintaining structural integrity and immune readiness through persistent B cell-stromal interactions. This research challenges the established paradigm of LN microarchitecture and suggests specialized niches for B cell function and lymphocyte trafficking in regions subject to constant antigenic exposure.